PENINGKATAN PENGETAHUAN STRATEGI PENGASUHAN PADA ANGGOTA DHARMA WANITA SMA N 1 TENGARAN MELALUI PSIKOEDUKASI PARENTING - Novita, Maria Prima; Purnomo, Jusuf Tjahjo; Rahayu, Maria Nugraheni Mardi; Kakampu, Winston Lovevinzy (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2024)
Being a parent can be both rewarding and challenging for adults. To be able to implement effective parenting, parents need to have various knowledge and understanding of their children's development and effective parenting strategies, especially in this modern era. On the other hand, not all parents have the knowledge and understanding of child development and effective parenting methods. Therefore, the community service team of the Faculty of Psychology collaborated with the Dharma Wanita Management of SMA N 1 Tengaran to conduct parenting psychoeducation aimed at Dharma Wanita members. This psychoeducation was conducted to increase parents' knowledge about child development and parenting strategies. After participating in this parenting psychoeducation activity, parents are expected to increase their knowledge and understanding of child and adolescent development, adolescent issues, and parenting strategies in the digital era. The results of the evaluation of the psychoeducation participants' reactions showed that this activity had material that suited the needs of the participants, was delivered clearly, had interesting content and was well organized.